2003
DOI: 10.1172/jci200318106
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of IL-10 in the induction of low zone tolerance to contact allergens

Abstract: MethodsMice. Mice deficient for IL-10 (IL-10 -/-mice), corresponding wild-type mice (IL-10 +/+ mice) on a C57BL/6 genetic background, genetically mast cell-deficient (MC-deficient) Kit W /Kit W-v mice, and The development and mechanisms of tolerance to allergens are poorly understood. Using the murine low zone tolerance (LZT) model, where contact hypersensitivity (CHS) is prevented by repeated topical low-dose applications of contact allergens, we show that LZT induction is IL-10 dependent. IL-10 is required f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2004
2004
2019
2019

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…It has been shown that ultraviolet B irradiation of the skin prior to allergen exposure, oral exposure to the allergen or skin exposure to low doses of the allergen can lead to allergen tolerance. [6][7][8] Although different mechanisms initiate the development of tolerance, they all lead to the induction of regulatory T cells (Tregs). [6][7][8] Different types of CD4+ Tregs have been described: naturally occurring CD4+CD25+Foxp3+ T cells, induced CD4+CD25+Foxp3+ T cells, and Tr1 and Th3 cells defined by prominent release of interleukin (IL)-10 and transforming growth factor (TGF)-b, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown that ultraviolet B irradiation of the skin prior to allergen exposure, oral exposure to the allergen or skin exposure to low doses of the allergen can lead to allergen tolerance. [6][7][8] Although different mechanisms initiate the development of tolerance, they all lead to the induction of regulatory T cells (Tregs). [6][7][8] Different types of CD4+ Tregs have been described: naturally occurring CD4+CD25+Foxp3+ T cells, induced CD4+CD25+Foxp3+ T cells, and Tr1 and Th3 cells defined by prominent release of interleukin (IL)-10 and transforming growth factor (TGF)-b, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…[6][7][8] Although different mechanisms initiate the development of tolerance, they all lead to the induction of regulatory T cells (Tregs). [6][7][8] Different types of CD4+ Tregs have been described: naturally occurring CD4+CD25+Foxp3+ T cells, induced CD4+CD25+Foxp3+ T cells, and Tr1 and Th3 cells defined by prominent release of interleukin (IL)-10 and transforming growth factor (TGF)-b, respectively. 9,10 All of these CD4+ Tregs are able to control the immune response to contact allergens by impeding the development and function of allergen-specific effector T cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…First, under the conditions at normal platelet counts, the ear swelling response was decreased at 24 hours after challenge in the mice with LZT than in those without LZT ( Figure S1A), as previously reported. [20][21][22] Furthermore, a histological examination revealed that the cell infiltration in the dermis was downregulated in the mice with LZT ( Figure S1B,C). In addition, the frequency of Foxp3 + Tregs among all infiltrating cells in the inflamed skin was increased in the mice with LZT ( Figure S2B).…”
Section: The Chs Response Of Lzt Micementioning
confidence: 97%
“…[20][21][22] In a model of LZT, IL-10-secreting regulatory CD4 + CD25 + Foxp3 + Treg cells evoke the generation of CD8 + suppressor/regulatory T cell, which prevent the induction of the contact hypersensitivity (CHS). [20][21][22] First, we showed that the repeated epicutaneous application of low doses of contact allergens suppressed the CHS responses with a high percentage of Foxp3 + Treg cells in the inflamed skin and draining lymph nodes (LNs). Next, we examined whether platelets were associated with the immune tolerance induction of the CHS responses, with or without platelet depletion during LZT.…”
Section: Introductionmentioning
confidence: 99%